Assembly-based conceptual 3D modeling with unlabeled components using probabilistic factor graph. (May 2016) - Jaiswal, Prakhar; Huang, Jinmiao; Rai, Rahul
Abstract: This work presents a novel and intuitive assembly based 3D modeling interface to support conceptual design exploration activities. In the presented modeling interface, unlabeled segmented components of the objects are assembled to create new 3D models. The development of the interface is motivated by two aspects. First, the focus is on novice users since they stand to gain the most from intuitive interfaces. Second, the intent is on creative reuse of a growing number and variety of 3D models available on vast online repositories like Turbosquid and Trimble 3D warehouse. Specifically, we have devised an automated component suggestion algorithm based on a probabilistic factor graph. This algorithm helps the user to easily browse and select components from a database that are most compatible with the current state of 3D models being assembled. The component suggestion algorithm incorporates various aspects such as shape similarity, repetitions of shapes, and adjacency relationships. Our new suggestive interface overcomes several limitations of traditional CAD interfaces by helping the users to quickly create and explore new conceptual designs. We present results on the conceptual design of several products. Highlights: We present a novel 3D CAD tool for conceptual design exploration. Interactive concept exploration through assembly-based 3D modeling paradigm. Automated component suggestion algorithm based on probabilistic factor graph. Creative reuse of 3D models available on vast online repositories.